Routine screening of antenatal population for thyroid disorders-mandatory - Hymavathi, Kaliki; Gottipati, Malini Devi; Jakka, Tejaswini; C., Bhavana T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Thyroid dysfunction is commonly seen in pregnant women causing adverse maternal and fetal effects. Routine screening of antenatal population for the same will be helpful for successful pregnancy outcomes. The objective of this study is to detect and treat antenatal women with Thyroid dysfunction to avoid deleterious maternal/ fetal effects. Methods: The present study is a hospital based prospective study conducted in the department of Obstetrics and Gynaecology of Narayana Medical College and Hospital(NMCH), Nellore, Andhra Pradesh, India. 1000 pregnant women were randomly recruited into this study. Apart from routine antenatal investigations, Thyroid function tests (TFT) - Thyroid stimulating hormone (TSH), freeT4 (fT4) and Thyroid peroxidase antibody (TPO Ab) are done for all the recruited women at the first visit of antenatal booking and individual Thyroid tests are repeated as required. Results: Following the TFT the study population is classified into pregnancies with euthyroidism‚ subclinical/ overt hypothyroidism and hyperthyroidism. The prevalence of Thyroid disorders in present study was 12.7% of which hypothyroidism noted in 10.3% (subclinical 6.9% and overt 3.4%) while hyperthyroidism seen in 2.4% (subclinical 1.8% and overt 0.6%). The various pregnancy complications, labour and neonatal outcomes have been analyzed. Conclusions: Thyroid dysfunction in pregnancy affects the health of the mother as well as the baby. Screening for Thyroid dysfunction should be performed as part of the routine antenatal work-up for successful pregnancy outcomes.